Effect of Business Analytics on Market Adaptation: Market Sensing and Product Management as Mediating Variables (International Journal of Applied Research in Management and Economics, 2023)
The study investigated the mediating roles of both market sensing and product management in the impact of business analytics on market adaptation in the eCommerce industry in Nigeria. A sample of 40 firms was selected using both probability and nonprobability sampling techniques. The questionnaire was used to elicit responses from the respondents and quantitative analysis was used to analyze the data collected from the survey. After the application of factors analysis to verify the both reliability and validity of the questionnaire, the result shows that product management has a significant mediating role in the relationship between business analytics and market adaptation while market sensing does not. This study recommends that firms particularly the ones in the eCommerce industry should allow business analytics to dictate changes to be made to their product lines, composition, and structure among others (product management), and by this, they will be able to adapt easily to changes in any market they find themselves.